Investigating EFL Kindergarten Teachers' Media and Challenges in Teaching Vocabulary - Rahmadan, Muhammad Kurniawan; Abrar, Mukhlash Abrar; Failasofah, Failasofah; Masbirorotni, Masbirorotni (Universitas Siliwangi, 2023)
These qualitative research purposes are to investigate EFL kindergarten teachers' media and challenges in teaching vocabulary. This research design was a qualitative method with a case study approach. The data was collected through interviews and audio-visuals with three participants from private kindergarten schools. The data was analyzed by thematic analysis. The findings revealed that they are similar to the media used by teachers. Most of them used printed properties and technology. Printed and properties are books and flashcards. Technology is software games, educational videos, television computer devices, songs, and games. The results of the study also indicated that the teachers faced some challenges when teaching vocabulary in the classroom, including challenges from students (noisy students, inclusive students, and students' mood), schools/institutions (lack of facility), and teachers themselves (classroom management and teachers' mood). Keywords: Challenges; EFL Teachers; Media; Vocabulary; Young Learners.